Smart Magnetic and Fluorogenic Photosensitizer Nanoassemblies Enable Redox‐Driven Disassembly for Photodynamic Therapy. (2nd September 2020) - An, Ruibing; Cheng, Xiaoyang; Wei, Shixuan; Hu, Yuxuan; Sun, Yidan; Huang, Zheng; Chen, Hong‐Yuan; Ye, Deju
Abstract: Stimuli‐responsive smart photosensitizer (PS) nanoassemblies that allow enhanced delivery and controlled release of PSs are promising for imaging‐guided photodynamic therapy (PDT) of tumors. However, the lack of high‐sensitivity and spatial‐resolution signals and fast washout of released PSs from tumor tissues have impeded PDT efficacy in vivo. Herein, we report tumor targeting, redox‐responsive magnetic and fluorogenic PS nanoassemblies (NP‐RGD ) synthesized via self‐assembly of a cRGD‐ and disulfide‐containing fluorogenic and paramagnetic small molecule (1‐RGD ) for fluorescence/magnetic resonance bimodal imaging‐guided tumor PDT. NP‐RGD show high r 1 relaxivity but quenched fluorescence and PDT activity; disulfide reduction by glutathione (GSH) promotes efficient disassembly into a small‐molecule probe (2‐RGD ) and an organic PS (PPa‐SH), which could further bind with intracellular albumin, allowing prolonged retention and cascade activation of fluorescence and PDT to ablate tumors. Abstract : Magnetic and fluorogenic photosensitizer nanoassemblies (NP‐RGD ) were constructed via self‐assembly of a cRGD‐ and disulfide‐containing small molecule (1‐RGD ). The nanoassemblies allowed the cascade activation of fluorescence/magnetic resonance bimodal imaging and on‐demand photodynamic therapy in the tumor through redox‐driven disassembly and in situ binding with albumin.